Contextual Factors That Enable and Restrain Social Network Formation of Dutch Erasmus+ Students - Schoe, Yentl; Van Mol, Christof; Buynsters, Michael (Journal of International Students, 2021)
When studying abroad, international exchange students generally establish a new social network abroad. However, how international exchange students develop their social networks over time remains a blind spot in the academic literature. In this paper, we therefore analyze the initial formation and development of such networks among six Dutch Erasmus+ students. Starting from homophily theory, we particularly focus on the factors that enable and restrain initial social network formation and interaction patterns. Methodologically, we rely on a longitudinal qualitative approach, whereby we repeatedly interviewed these six students over time. Our findings reveal the importance of three main contexts in the initial social network formation of Erasmus+ students, namely the pre-mobility phase, the living place, and the social space. These findings provide insights for practitioners on which contexts to focus on when developing strategies to foster the integration of international exchange students at host institutions.